Integrated waste recycling framework for municipal solid waste generated (MSWG) in Bauchi Metropolis, Nigeria - Isa Harir, Adamu; Kasim, Rozilah (JASES, 2017)
An audit survey of quantities and compositions of municipal solid waste generated (MSWG) is important to plan an effective waste management in any locality. Resource recycling of solid waste materials is more preferable than waste disposal in landfills, which is the last choice consideration. In Bauchi metropolis, the resource recycling possibilities from MSWG are rarely explored as evident in the observed mixed waste disposed-off in the final dump sites in the study area. In Bauchi as in most Nigerian cities mixed waste is disposed without segregation into open dump sites as a typical method for waste management. This study has investigated the MSWG in Bauchi metropolis and explored the possibilities of integrated waste recycling (IWR) due mainly to lack of waste characterisation studies. An IWR system combines recycling with composting methods as a strategy to achieve optimum recovery of inorganic and organic wastes respectively from the MSWG. This study is a quantitative analysis of MSWG in the three residential zones within Bauchi metropolis. Stratified random method was used to select 400 household units as sample size for data collection and 368 of the screened data was found valid for detail analysis. The result revealed waste composition that supported IWR method and can recover up to 76.55% of MSWG in Bauchi the study area. This study concludes that IWR possibilities are large from the compositions of MSWG in Bauchi metropolis. Therefore, IWR framework is proposed to implement these possibilities as a prelude to effective management for MSWG in Bauchi metropolis, Nigeria.